Meteorological data from ice-free areas in Yukidori Zawa, Langhovde and Kizahashi Hama, Skarvsnes, and Skallen on Soya Coast, East Antarctica during January 2017 - December 2018 ... - Kudoh, Sakae; Wada, Tomotake; Shimada, Shou; Otani, Mashiro; Elster, Josef; Uchida, Masaki; Imura, Satoshi (Arctic Data archive System (ADS), Japan, 2021)
Meteorological data recorded by automatic weather stations (AWSs) in the Yukidori Zawa (Yukidori Valley), Langhovde, and in Kizahashi Hama, Skarvsnes on the Soya Coast of East Antarctica ...